Continue with your mobile number
M^(-1) L^3 T^2 Gravitational Force = G × (M1 ×M2)/R² (Where R is Distance) Dimension of Force = MLT^(-2) = G × M²/L² G = MLT^(-2) × L²/M² G = M^(-1) L^3 T^(-2)
Statements: X ≥ W > O = F ≥ B ≥ J; M < A ≤ J
Conclusions:
I. M < B
II. O ≥ A
III. O < A
...Statements: O ≤ R ≤ N ≥ H > K; U < Q ≤ N ≤ B
Conclusions :
I. H ≥ Q
II. R < U
Statements: U = R < M < Q < P; A > B > E < R < T; I < N = B > U > X
Conclusions:
I.  P ≤ U
II. Â T > A
...Statements: D = E ≥ G = K, O > B ≤ C = K, E ≤ I < F
Conclusions: I. K > O II. D ≥ C
...Statements: O ≥ M > F, K ≤ J ≤ D = F, B ≤ Z ≤ L = K
Conclusion:
I. M > L
II. D ≥ B
Statements: Â MÂ @ C, C $ X,X # J, JÂ * Â NÂ Conclusions :Â
I.        N % X
II.       J % MÂ
Statements: K * D, D $ N, N % M, M © W
Conclusions: Â Â Â Â Â I.M % WÂ Â Â Â Â Â Â Â Â Â Â Â Â Â II.M $ WÂ Â Â Â Â Â Â Â Â Â Â Â Â III.N @ DÂ...
Statement: X≤Y<W =Z ≤U<S;S>T ≥V
I. Z≥T
II. Z > X
Statements: A > E ≤ B; G < C ≤ E; D < C ≤ F
Conclusions:
I. D < B
II. F ≤ E
III. A > G
...Statements: U = V ≤ W > Q ≥ N; B < Q; E = W
Conclusion: I. E > Q II. W > B
...